2012
DOI: 10.4236/jasmi.2012.24031
|View full text |Cite
|
Sign up to set email alerts
|

System for High Throughput Water Extraction from Soil Material for Stable Isotope Analysis of Water

Abstract: A major limitation in the use of stable isotope of water in ecological studies is the time that is required to extract water from soil and plant samples. Using vacuum distillation the extraction time can be less than one hour per sample. Therefore, assembling a distillation system that can process multiple samples simultaneously is advantageous and necessary for ecological or hydrological investigations. Presented here is a vacuum distillation apparatus, having six ports, that can process up to 30 samples per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 16 publications
4
30
0
Order By: Relevance
“…Because of Rayleigh fractionation, we found progressively less negative values towards the end of the extraction process for both isotopes (exception: δ 18 O after 45 min extraction time). In agreement with the results of West et al (2006) and Goebel and Lascano (2012), we observed no statistically significant changes in the isotopic signatures for extraction times longer than 30 min for hydrogen isotopes and 60 min for oxygen isotopes for this specific soil type. Nevertheless, as already observed in experiment #4 neither δ 2 H nor δ 18 O of extracted water matched the isotopic signature of the applied water.…”
Section: Experiments 5: Effect Of Extraction Timesupporting
confidence: 91%
See 3 more Smart Citations
“…Because of Rayleigh fractionation, we found progressively less negative values towards the end of the extraction process for both isotopes (exception: δ 18 O after 45 min extraction time). In agreement with the results of West et al (2006) and Goebel and Lascano (2012), we observed no statistically significant changes in the isotopic signatures for extraction times longer than 30 min for hydrogen isotopes and 60 min for oxygen isotopes for this specific soil type. Nevertheless, as already observed in experiment #4 neither δ 2 H nor δ 18 O of extracted water matched the isotopic signature of the applied water.…”
Section: Experiments 5: Effect Of Extraction Timesupporting
confidence: 91%
“…Incomplete water extraction in terms of weight was only observed for one sample, with a recovery rate still as high as 99 %. West et al (2006) determined extraction times to obtain an unfractionated water sample for sandy soils of 30 min, and 40 min for clay soils, consistent with the results of Goebel and Lascano (2012) who recommended 30 min extraction duration for a sandy clay loam. Koeniger et al (2011) applied even shorter extraction times (2.5 to 40 min), recovering the original water isotopic signature after 15 min.…”
Section: Experiments 6: Effect Of Soil Typesupporting
confidence: 72%
See 2 more Smart Citations
“…Three petioles were sampled and reduced in size to ~13 mm, placed in an 8 mL glass screw top vial, sealed and stored in the freezer until time for extraction. To begin the extraction procedure the stored vials were removed from the freezer, the caps were removed and both the caps and the vials were placed into an ignition tube (Pyrex ® , 25 × 200 cm) and a rubber stopper was used to seal the ignition tube [33] The tube was then placed in liquid nitrogen (LN 2 ) for 20 minutes prior to placement on the distillation apparatus. The ignition tube was then placed on the distillation apparatus and vacuum was applied until the pressure read <13 Pa.…”
Section: Extraction Of Petiole Watermentioning
confidence: 99%